Educational leadership and the sustainable development of martial arts education in Chinese secondary schools: evidence from Xiaoshan, Hangzhou - Shao, Yinshuang; Basar, Annisaa (Frontiers in Education, 2025)
This study examines the influence of school leadership and educational administration on the sustainable implementation of martial arts education in secondary schools, utilizing Xiaoshan District, Hangzhou, as a case study. Despite national initiatives to integrate martial arts into formal curriculum, implementation is constrained by inadequate teacher credentials, insufficient facilities, lack of institutional prioritization, and little community involvement. A quantitative assessment of 200 students and 15 physical education teachers from four schools indicated that hardly 20% of the institutions provide mandatory martial arts lessons, none has specialized equipment, and no instructors are professionally certified. More than fifty percent of the educators recognized insufficient leadership focus, finance, and parental involvement as significant obstacles. The results indicate that schools with proactive leadership have enhanced resource allocation, teacher support, and student involvement. The research supports localized training systems, culturally attuned curricula, and family-school collaborations to enhance sustainability. It provides comprehensive insights into how educational leadership can close the policy–practice divide and facilitate culturally relevant curricular innovation in many educational environments.